2021
DOI: 10.1210/clinem/dgab598
|View full text |Cite
|
Sign up to set email alerts
|

Production of 11-Oxygenated Androgens by Testicular Adrenal Rest Tumors

Abstract: Context Testicular adrenal rest tumors (TART) are a common complication in males with classic 21-hydroxylase deficiency (21OHD). TART are likely to contribute to the androgen excess in 21OHD patients, but a direct quantification of steroidogenesis from these tumors has not been yet done. Objective Define the production of 11-oxygenated 19-carbon (11oxC19) steroids by TART. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Although it has been shown that 11β-hydroxysteroid dehydrogenase types 1 and 2 are expressed in testicular Leydig and ovarian theca cells ( 15 ), our findings contradict the idea that gonadal 11-KT production significantly contributes to the systemic pool in females because CYP11B1 is usually only expressed in negligible amounts in the gonads ( 23 ). An exception to this are patients with CAH in which aberrant adrenal tissue can be found within the testicles or ovaries ( 24 , 25 ). The idea that 11-KT is produced in peripheral tissue from 11-OHA4 produced in the adrenal is supported by the observation that 11-KT levels did not differ between the sampling sites, considering the significantly higher 11-OHA4 levels in the adrenal vein samples, especially.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that 11β-hydroxysteroid dehydrogenase types 1 and 2 are expressed in testicular Leydig and ovarian theca cells ( 15 ), our findings contradict the idea that gonadal 11-KT production significantly contributes to the systemic pool in females because CYP11B1 is usually only expressed in negligible amounts in the gonads ( 23 ). An exception to this are patients with CAH in which aberrant adrenal tissue can be found within the testicles or ovaries ( 24 , 25 ). The idea that 11-KT is produced in peripheral tissue from 11-OHA4 produced in the adrenal is supported by the observation that 11-KT levels did not differ between the sampling sites, considering the significantly higher 11-OHA4 levels in the adrenal vein samples, especially.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that TART tissue actively synthesizes steroids. Besides the production of 17OHP, 21dF, and progesterone, TART tissue can contribute to the production of adrenal androgens, including 11-oxygenated androgens (137)(138)(139).…”
Section: Tartmentioning
confidence: 99%
“…Likewise, blood levels of 11-KT and other 11-oxyandrogens were increased in patients with 21-OHD and testicular adrenal rest tumors (TART) ( 27 ). Steroid measurement of spermatic vein blood samples suggested that TART can produce various 11-oxyandrogens ( 28 ). Particularly the high levels of 11-OHT in the spermatic vein blood samples of patients with TART ( 28 ) are indicative of high CYP11B1 activity in these tumors.…”
Section: Pathophysiological Roles Of 11-oxyandrogens From the Viewpoi...mentioning
confidence: 99%
“…Steroid measurement of spermatic vein blood samples suggested that TART can produce various 11-oxyandrogens ( 28 ). Particularly the high levels of 11-OHT in the spermatic vein blood samples of patients with TART ( 28 ) are indicative of high CYP11B1 activity in these tumors.…”
Section: Pathophysiological Roles Of 11-oxyandrogens From the Viewpoi...mentioning
confidence: 99%